Sao Tome and Principe : Joint Staff Advisory Note on the Poverty Reduction Strategy Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2008)
The second Annual Progress Report (APR) evaluates progress of Poverty Reduction Strategy Paper (PRSP) implementation aimed to promote growth and reduce poverty of Sao Tome and Principe. The report recognizes the need to tighten fiscal and monetary policies to safeguard macroeconomic stability, emphasize on strengthened implementation of public financial management reforms, and achieve MDGs, particularly in health and education. It also stressed the need to review oil prospects in future reports. The APR emphasizes on the importance of debt relief, strong policy implementation, and greater coordination with the country's development partners.